Financial inclusion strategy in Cali, Colombia - Escobar Zúñiga, Víctor Manuel (RAN - Revista Academia & Negocios, 2020)
This paper presents a case study whose aim is the design of a Financial Education model, implemented in a microfinance institution, with a focused strategy of social intervention to a segment of vulnerable people in Cali. Through this strategy, the most accepted lines of intervention to be implemented in the financial education model are validated and identified. This situated and directed intervention contributes to the improvement of the life quality of people, specially those who do not have enough economic resources to finance their microenterprise activities. The paper also discusses the international microfinance theories, which support the conceptual study of the financial education model. Likewise, the methodology used and the results of the different investigative stages are presented, among them the development of a pilot study that specifies the orientation line of the Financial Doctor, and its espective implementation, articulated with the phases of demographic social characterization of the population of Cali, as well as the diagnosis of the financial situation of clients who attended the financial consultation.